The ankyrin repeat domains of the NF-kappa B precursor p105 and the protooncogene bcl-3 act as specific inhibitors of NF-kappa B DNA binding. - Hatada, E N (1992)
The inducible pleiotropic transcription factor NF-kappa B is composed of two subunits, p50 and p65. The p50 subunit is encoded on the N-terminal half of a 105-kDa open reading frame and contains a rel-like domain. To date, no function has been described for the C-terminal portion. We show here that the C-terminal half of p105, when expressed as a separate molecule, binds to p50 and can rapidly disrupt protein-DNA complexes of p50 or native NF-kappa B. Deletion analysis of this precursor-derived inhibitor activity indicated a domain containing ankyrin-like repeats as necessary for inhibition. The protooncogene bcl-3, which contains seven ankyrin repeats, can equally inhibit p50 DNA binding. These observations identify bcl-3 as an inhibitor of NF-kappa B and strongly suggest that the ankyrin repeats in these factors are involved in protein-protein interactions with the rel-like domain of p50. Comparison with other ankyrin repeat-containing proteins suggests that a subclass of these proteins acts as regulators of rel-like transcription factors.